2014
DOI: 10.1007/s11999-014-3944-8
|View full text |Cite
|
Sign up to set email alerts
|

Does Fluoroscopy Improve Acetabular Component Placement in Total Hip Arthroplasty?

Abstract: Background The success of THA largely depends on correct placement of the individual components. Traditionally, these have been placed freehand using anatomic landmarks, but studies have shown poor accuracy with this method. Questions/purposes Specifically, we asked (1) does using fluoroscopy lead to more accurate and greater likelihood of cup placement with the Lewinnek safe zone than does freehand cup placement; (2) is there a learning curve associated with the use of fluoroscopy for cup placement; (3) does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 23 publications
2
53
0
Order By: Relevance
“…Intra-operative fluoroscopy allows real-time assessment of implant positioning and has been shown to improve component positioning when compared to freehand techniques. 15 Poor component positioning has been associated with increased risk of dislocation, decreased range of motion, increased concentration of metal ions after resurfacing, and increased risk of polyethylene wear. 1619 Other studies have compared post-operative acetabular inclination and acetabular anteversion between the DAA with intra-operative fluoroscopy and the posterior approach.…”
Section: Introductionmentioning
confidence: 99%
“…Intra-operative fluoroscopy allows real-time assessment of implant positioning and has been shown to improve component positioning when compared to freehand techniques. 15 Poor component positioning has been associated with increased risk of dislocation, decreased range of motion, increased concentration of metal ions after resurfacing, and increased risk of polyethylene wear. 1619 Other studies have compared post-operative acetabular inclination and acetabular anteversion between the DAA with intra-operative fluoroscopy and the posterior approach.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple techniques have been promoted to enhance the accuracy of component positioning, including the use of fluoroscopy [1,2,24], computer navigation [31,32], and robotic assistance [5,6]. Of these three, fluoroscopy is the most widely available and least expensive to adopt.…”
Section: Discussionmentioning
confidence: 99%
“…It's unclear if the improvement in that sense was due to the use of fluoroscopy or the change in approach. Beemer et al [2] demonstrated that the use of fluoroscopy can improve component position in the posterior approach. Our results demonstrate that when using fluoroscopy in the anterior approach, we achieved better results than when used in the posterior approach (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations